Correction: Expanding plastics recycling technologies: chemical aspects, technology status and challenges. Issue 23 (17th November 2022) - Li, Houqian; Aguirre-Villegas, Horacio A.; Allen, Robert D.; Bai, Xianglan; Benson, Craig H.; Beckham, Gregg T.; Bradshaw, Sabrina L.; Brown, Jessica L.; Brown, Robert C.; Cecon, Victor S.; Curley, Julia B.; Curtzwiler, Greg W.; et al.
Abstract : Correction for 'Expanding plastics recycling technologies: chemical aspects, technology status and challenges' by Houqian Li et al., Green Chem., 2022, ; https://doi.org/10.1039/d2gc02588d .